English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2 answers

Prove the identity: 2secA = cosA/(1 + sinA)

We'll work with the right hand side.

cosA/(1 + sinA) + (1 + sinA)/cosA
= cosA(1 - sinA)/{(1 + sinA)(1 - sinA)} + (secA + tanA)
= cosA(1 - sinA)/(1 + sin²A) + (secA + tanA)
= cosA(1 - sinA)/cos²A + (secA + tanA)
= (1 - sinA)/cosA + (secA + tanA)
= (sec A - tanA) + (secA + tanA) = 2secA = LHS
__________________________

Prove the identity: (secA - 1)/(secA + 1) = (1 - cosA)²(csc²A)

We'll work with the right hand side.

(1 - cosA)²(csc²A) = (1 - cosA)²/sin²A = (1 - cosA)²/(1 - cos²A)
= (1 - cosA)²/{(1 - cosA)(1 + cosA)} = (1 - cosA)/(1 + cosA)
= (secA - 1)(secA + 1) = LHS

2007-01-26 12:32:10 · answer #1 · answered by Northstar 7 · 1 0

(cosA/(1 + sinA)) + ((1 + sinA)/cosA)
((cosA * cosA) + ((1 + sinA)(1 + sinA)))/(cosA * (1 + sinA))
((cos(A))^2 + (1 + sinA + sinA + (sin(A))^2)/(cosA * (1 + sinA))
((1 - sin(A)^2) + (1 + 2sinA + sin(A)^2))/(cosA * (1 + sinA))
(1 - sin(A)^2 + 1 + 2sinA + sin(A)^2)/(cos(A) * (1 + sinA))
(2 + 2sin(A))/(cos(A) * (1 + sin(A)))
2(1 + sin(A))/(cos(A) * (1 + sin(A)))
2/cosA

ANS : 2/cosA or 2sec(A)

---------------------------------------------------------------

(sec(A) - 1)/(sec(A) + 1) = (1 - cos(A))^2 * csc(A)^2

((1/cosA) - 1)/((1/cosA) + 1)
((1 - cosA)/cosA) / ((1 + cos(A))/cosA)
((1 - cosA)/cosA) * (cosA/(1 + cosA))
(1 - cosA)/(1 + cosA)

(1 - cosA)^2 * csc(A)^2
(1 - cosA)(1 - cos(A)) * (1/sinA)^2
((1 - cosA)(1 - cosA))/(sin(A)^2)
((1 - cosA)(1 - cosA))/(1 - cos(A)^2)
((1 - cosA)(1 - cosA))/((1 - cosA)(1 + cosA))

one set of the (1 - cosA)s cancel out

(1 - cosA)/(1 + cosA)

so since both sides equal (1 - cosA)/(1 + cosA)

(sec(A) - 1)/(sec(A) + 1) = (1 - cos(A))^2 * csc(A)^2

2007-01-26 23:03:32 · answer #2 · answered by Sherman81 6 · 0 0

fedest.com, questions and answers